Terminating life-sustaining treatment--recent US developments - Mackay, R. D. (Journal of medical ethics, 1988)
This paper reviews some recent litigation in the United States which addresses the difficult question of withdrawing food and hydration from both competent and incompetent patients. Whilst the decisions in question have manifested a trend towards favouring patient autonomy, they also indicate an underlying tension between doctors, health care facilities and their dying patients which is not yet close to resolution. The author suggests that the courts in the United States are likely to remain, for the foreseeable future, the final arbiters in that country of disputes relating to the termination of life-sustaining treatment.